World Development Report 1992 : Development and the Environment - World Bank (New York: Oxford University Press, 2012)
This is the fifteenth in the annual series assessing major development issues. The World Development Report 1992 explores the links between economic development and the environment. The 1990 report on poverty, last year's report on development strategies, and this report constitute a trilogy on the goals and means of development. The main message of this year's report is the need to integrate environmental considerations into development policymaking. The report argues that continued, and even accelerated, economic and human development is sustainable and can be consistent with improving environmental conditions, but that this will require major policy, program, and institutional shifts. A twofold strategy is required. First, the positive links between efficient income growth and the environment need to be aggressively exploited. Second, strong policies and institutions need to be put in place which cause decision makers to adopt less damaging forms of behavior. Where tradeoffs exist between income growth and environmental quality, the report argues for a careful assessment of the costs and benefits of alternative policies. This approach will result in much less environmental damage. Like its predecessors, this report includes the World Development Indicators, which offer selected social and economic statistics on 125 countries.